2023
DOI: 10.1021/jacs.3c00831
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Selenocysteine Substitutions Reveal Direct Substrate–Enzyme Interactions at Auxiliary Clusters in Radical S-Adenosyl-l-methionine Maturases

Abstract: Radical S-adenosyl-l-methionine (SAM) enzymes leverage the properties of one or more iron- and sulfide-containing metallocenters to catalyze complex and radical-mediated transformations. By far the most populous superfamily of radical SAM enzymes are those that, in addition to a 4Fe–4S cluster that binds and activates the SAM cofactor, also bind one or more additional auxiliary clusters (ACs) of largely unknown catalytic significance. In this report we examine the role of ACs in two RS enzymes, PapB and Tte118… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…While the data with hCys, hGlu, and D-amino acid containing peptides all suggest a high level of tolerance in PapB for various substrates, the examples shown are limited by the fact that they all contain a thiol- and carboxylate-containing residue. We have demonstrated that selenocysteine peptides are processed by PapB, but as far as we are aware, no examples of an isostere of a carboxylate moiety being processed by an rSAM RiPP maturase are known. Tetrazole moieties are commonly used as bioisosteric replacements for carboxylic acid moieties in small-molecule drug development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the data with hCys, hGlu, and D-amino acid containing peptides all suggest a high level of tolerance in PapB for various substrates, the examples shown are limited by the fact that they all contain a thiol- and carboxylate-containing residue. We have demonstrated that selenocysteine peptides are processed by PapB, but as far as we are aware, no examples of an isostere of a carboxylate moiety being processed by an rSAM RiPP maturase are known. Tetrazole moieties are commonly used as bioisosteric replacements for carboxylic acid moieties in small-molecule drug development.…”
Section: Resultsmentioning
confidence: 99%
“…The Fe-S clusters and SAM cofactor can be readily modeled into PapB based on their location in CteB. Further, a truncated and energy minimized version of the peptide can be docked with constraints based on known interaction of auxiliary cluster 1 (AC1) with the thiolate side chain . This model predicts that the carboxylate moiety of the msPapA peptide interacts with H377 and R378 of PapB.…”
Section: Discussionmentioning
confidence: 99%
“…Structurally intriguing natural products are routinely identified as being formed by radical S -adenosylmethionine (rSAM) enzymes, which constitute one of the largest and most diverse enzyme superfamilies (Pfam entry PF04055). Within the rSAM active site, an oxidatively labile [4Fe-4S] center reductively cleaves SAM to produce l -methionine and 5′-deoxyadenosyl radical (5′-dAdo·). , Hydrogen atom abstraction from the substrate by 5′-dAdo· propagates a radical cascade from which different reaction pathways are available to generate the final product(s). , As compiled by the web-based repository , ∼100,000 rSAM enzymes contain one or more additional [Fe–S] centers and are classified as members of the SPASM/twitch group. ,, These auxiliary [Fe–S] centers are proposed to aid in substrate alignment and facilitate electron transfer. Within RiPP biosynthesis, rSAM enzymes catalyze numerous modifications, including methylation, carbon–carbon and carbon–sulfur cross-linking, epimerization, and more. , …”
Section: Introductionmentioning
confidence: 99%
“…5,9,10 These auxiliary [Fe-S] centers are proposed to aid in substrate alignment and facilitate electron transfer. [11][12][13] Within RiPP biosynthesis, rSAM enzymes catalyze numerous modifications, including methylation, carbon-carbon and carbon-sulfur crosslinking, epimerization, and more. 1,[14][15][16][17][18][19][20][21][22][23][24][25] Darobactin A is a twice-cyclized rSAM-modified RiPP (Figure 1).…”
Section: Introductionmentioning
confidence: 99%